The effect of social and economic transitions on the meaning of work: A cross-sectional study among Israeli employees. Issue 4 (3rd June 2019) - Sharabi, Moshe; Polin, Brian; Yanay-Ventura, Galit
Abstract : Purpose: The purpose of this paper is to examine the impact of social and economic changes, particularly the transition from a collectivistic to an individualistic society, on the meaning of work (MOW) in Israel. Design/methodology/approach: A questionnaire probing the MOW domains (economic orientation, intrinsic orientation, interpersonal relations, entitlement and obligation norms and job satisfaction) was conducted on a representative sample of the Israeli labor force in 1981 ( n =973) and 2006 ( n =898). Findings: A comparison between the results of the 1981 and 2006 surveys shows a significant increase in economic and intrinsic orientation, and a significant decrease in interpersonal relations orientation, job satisfaction and obligation and entitlement norms. Work centrality remained stable. The demographic factors, especially education, have some impact on the MOW domains. Practical implications: The transformation of work values reflects the changes in employees' expectations and needs. Therefore, organizations are compelled to find new material and non-material reward systems and methods to maintain employee commitment, motivation and satisfaction. Various implications for organizations and management are discussed. Originality/value: This cross-sectional study explores how the combination of economic and social changes is reflected in employees' job satisfaction and other work values. Furthermore, the study examines the impact of the main demographic factors on the MOW and offers suggestions to gain employees loyalty and commitment based on all the findings.